GAMBARAN PENYAKIT INFEKSI SALURAN PERNAFASAN AKUT PADA BALITA DI PUSKESMAS KASIHAN II BANTUL YOGYAKARTA - Nur Hasanah (PSIK 11 UMY, 2011)
Acute respiratory tract infection (ARI) is one cause of children death in developing countries. ARI causes 4 of 15 million deaths in children under 5 years each year. This study aimed to know the description of acute respiratory infection disease in toddler at Kasihan II Primary Health Care Bantul Yogyakarta. This study was a descriptive research, non experiment, with cross sectional approach. It used purposive sampling technique that collected 84 respondents.This study was conducted in Kasiha